The impacts of peer education based on adolescent health education on the quality of life in adolescents: a randomized controlled trial - Diao, Hua; Pu, Yang; Yang, Lianjian; Li, Ting; Jin, Feng; Wang, Hong (Quality of life research, 2020)
Purpose During adolescence, adolescents are more susceptible to internalizing and externalizing problems influencing quality of life (QoL). The purpose of the study is to verify the effectiveness of a peer education on improving QoL of adolescents. Methods A cluster randomized controlled trial (RCT) was conducted involving 1564 subjects who were divided into an intervention group ( n = 714) and a control group ( n = 850). The intervention group received 1-year peer education. Their QoL and basic information were assessed using a Adolescent Quality of Life Scale and a self-designed basic situation questionnaire. Results After the intervention, significant increases were found in the psychological, and social, pubertal dimensions, and in total QoL ( P < 0.05) in the intervention group relative to the control group. Significant decrease was found in physical dimension ( P < 0.05), but the change in the intervention group (0.74 decrease) was much less than that in the control group (1.94 decrease). The improvements of physical ( B = 1.215, SE = 0.305, P < 0.001), psychological ( B = 1.496, SE = 0.598, P = 0.013), pubertal ( B = 0.828, SE = 0.244, P = 0.001), and total ( B = 3.455, SE = 1.429, P = 0.016) QoL in the intervention group were higher than in the control group in mixed model. Conclusions The peer education based on adolescent health education is effective in improving the physical, psychological, pubertal, and total QoL of adolescents, but no social QoL.